Didactic strategies used in remote presence at Universidad Nacional’s Education for Work Division during pandemic times (Innovaciones Educativas, 2020)
The article presents the didactic strategies used in the Division of Education for Work (DET) of Universidad Nacional (UNA) in Costa Rica to implement remote presence as a response to the changes in the educational processes produced by the virus responsible for COVID-19. To specify the above, the teaching staff and students of the aforementioned Academic Unit participated during the first cycle and the first part of the second cycle of 2020, through a quantitative study with a non-probabilistic sample of voluntary participants through the survey technique. It was determined that the strategies put into practice by the teachers were opportune to produce the desired effect (learning from remote presence) in the lived context, given that the didactic proposals were diversified towards the student body and the perception of this was that. The learning objectives of the different subjects of the Baccalaureate and Bachelor's Degree in Guidance were achieved, and it also allowed an intensive use of technological resources to mediate learning. Finally, the study demonstrated the need to clarify the conceptualization of remote learning in academic staff, in addition to delving into future research processes that allow reflection on other elements of this modality, such as its curricular relevance, technological and pedagogical access.
Keywords: Educational strategies; learning; teaching; higher education; didactic strategies; remote presence; COVID-19